Penser la ressource minière en Nouvelle-Calédonie. Souveraineté, développement et valeur des lieux - Claire Levacher (Développement Durable et Territoires)
In New-Caledonia, the management and governance of mining resources in a long view challenge the local state for a decade. This French territory is currently engaged in a decolonization process, which partly rests upon the development of news mining industrial plants. Meanwhile, this last ten years both mining and environmental law were drawn up. This article focuses on the Goro-Nickel mining project in the South of the country, mobilizations it has produced, and their effects upon the regulation of mining resources. Mainly based upon a doctoral research, this paper questions more largely the exercise of sovereignty in New Caledonia through the expressions of several values the mobilization has raised, especially regarding the place of the mining project, and how they can explain the signature of an impact and benefits agreement between indigenous communities and the mining operator.